Simulation analysis of probabilistic covert channels based on probabilistic interference - GUO Yun-chuan1; ZHOU Yuan3; DING Li3; GUO Li1 (Tongxin xuebao)
Bandwidth and transmission error rate has received much attention in fields of covert channels.If a system does not satisfy BSPNI,PBNDC or SPBNDC property,then probabilistic covert channels will be formed.A simulation system was built to analyze their bandwidth and transmission error rate about covert channels.For every results of simulation,detail theoretical explanations were given.The results show the bandwidth is closely related to software/hardware configuration,probability pa-rameter and scheduling times,when configurations and probability parameter are fixed,the bandwidth is inversely propor-tional to scheduling times.For the same process,the greater is scheduling times,the smaller is transmission error rate.